Analisis Volume Saham Campina Ice Cream Industry Tbk. (ISSI): Regresi dengan Teknik Imputasi LOCF: Regresi dengan Teknik Imputasi LOCF - Pandu Dewanata (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
PT Campina Ice Cream Industry Tbk is an ice cream manufacturer headquartered in Surabaya. To support all company activities and optimize the operations of the Campina company until the end of 2020. Analyzing the stock price index and the volume of shares of the Campina company during the COVID-19 pandemic through several regression assumption model simulations by suppressing the imputation in the company data and estimating the missing data value by The LOCF imputation technique started from early 2020, which was the beginning of confirmed covid until now in April 2022 so that it can be used as a data reference for investors to see the performance and strategies carried out during covid and also see graphs and statistics on the performance of the Campina company. And we did some regression assumption model tests. including normality test, heteroscedasticity test, multicorrelation test, autocorrelation test, linearity test. And we found quite good results regarding the volume of stock prices before and after amputation with the LOCF technique, not too much change, but we found the best model for regression was in the fourth simulation. So that accountants and stock investors can use the data we obtained for material to considering the original condition of the company during this covid 19.